Best Shallow Draft Sailboats (2026)
If you’re shopping for a sailboat in Florida, the Bahamas, the Chesapeake, the Gulf Coast, or anywhere with shallow creeks, canals, sandbars, and skinny-water marinas, draft might be the most important number on the spec sheet. In this video, we look at the best shallow draft sailboats for real-world cruising, including production monohulls you can actually find used today. We talk about Island Packet, Catalina, Bristol, Hunter, and Beneteau models that make sense for sailors who need a shoal draft sailboat that can handle thin water without becoming a strange one-off unicorn boat. We’ll cover shallow draft cruising boats like the Island Packet 31, Catalina 30 wing keel, Catalina 28 MkII, Catalina 270, Bristol 29.9 centerboard, Bristol 35.5C, Hunter 306 shoal draft, Beneteau Oceanis 281, and Beneteau First 285. We’ll also explain the difference between wing keels, sho